Abstracting the Debate over Fair Value Measurement and Arm's Length Principle: Implications for Tax Purposes - Prianto Budi Saptono; Ismail Khozen (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: The requirement for a transaction price measurement system that accurately reflects actual value is becoming increasingly urgent as firms expand globally. The argument over the applicability of fair value (FV) and arm's length principle (ALP) arose since both are applicable concurrently due to their broad confluence. This study analyzes and synthesizes the similarities and distinctions, as well as the impact of FV and ALP on tax purposes.Method: The study is descriptive qualitative in nature. We gathered data through document analysis and in-depth interviews. Five informants from academics, policymakers, and tax practitioners were involved in the study. Before the interview, we familiarized the outline to decrease the random error, and all informants gave verbatim consent.Findings: An outline of the relationship between FV and ALP and their origins is provided. The direction in which the two procedures are designated is crucial, even though they can be employed concurrently to accomplish the entity's objectives, one for financial reporting and the other for transfer pricing. The narrative describing the similarities and contrasts between the two methods also plays a role in the analysis. It discusses the significance of the long-established ALP regime to FV, which has recently gained much attention even though it appears to be new. Finally, prudence in taking policies related to the harmonization of FV and ALP is an emphasis on considering the consequences for tax purposes. ALP is more often acknowledged by tax administration than FV. Implementing FV for tax purposes is discussed, along with related considerations.Novelty: The contribution of this work is a more brief and straightforward understanding of the business environment and the literature regarding FV and ALP. In contrast to the overarching goal of prior works, the current study analyzes the impact of FV and ALP adoption on taxation.